2021
DOI: 10.1111/psyg.12663
|View full text |Cite
|
Sign up to set email alerts
|

Gender difference about death anxiety among older adults: Structural Equation Model

Abstract: Background Older adults may be more prone to death anxiety than their younger counterparts. This study explores factors affecting death anxiety based on gender differences. Methods In this correlational study, 450 older adults referred to the health centres in the city of Bukan, Iran were recruited by using a randomised sampling method. Next, data were collected about the demographic questionnaire, anxiety about ageing, death anxiety, mental well‐being, perceived social support, and quality of life questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 34 publications
(61 reference statements)
4
8
0
Order By: Relevance
“…Continuing with the symptomatology derived from anxiety, it is observed that females show higher scores for each of the symptoms. Tese results may be due to neuroendocrine responses to a traumatic or stressful situation [36]. Also, in recent years it has been found that the amygdala and the hippocampus are highly involved in emotional control in the face of a stressful response [37,38], concluding that the amygdala is greater in men and the hippocampus greater in women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Continuing with the symptomatology derived from anxiety, it is observed that females show higher scores for each of the symptoms. Tese results may be due to neuroendocrine responses to a traumatic or stressful situation [36]. Also, in recent years it has been found that the amygdala and the hippocampus are highly involved in emotional control in the face of a stressful response [37,38], concluding that the amygdala is greater in men and the hippocampus greater in women.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these results, it is established that women abandon physical sports practice early, which has a negative impact on their body image [34,35]. Likewise, young adolescents who have practised sports at an early age develop a more favourable physical capacity and feelings about their own body image [36].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also shown differences according to gender and or age (e.g. Adelirad et al, 2021;Ansari & Lankarani, 2016;Dadfar et al, 2021;Pierce et al, 2007;Saeed & Bokharey, 2016). Abdel-Khalek (2003), for example, noted significant differences between countries and between genders, attributing their cause to the cultural issues of individualism vs. collectivism (Hofstede, 1980;Triandis 1995) or to socially established differences in contrasting groups of countries.…”
Section: Cultural Variation In Death Anxietymentioning
confidence: 98%
“…It is viewed as a predictor for both the existence and severity of mental diseases [22]. Couple of studies have been launched to examine the association between death anxiety and well being of the aged [23], cancer patients [24], multiple sclerosis [25] and the victims of COVID-19 [26,27]. Death anxiety during the pandemic is reported high and associated with the death of a family member from COVID- Conclusively, previous studies assessed the overall impact of the pandemics on mental health, proposing a general outlook towards psychological impact of COVID-19.…”
Section: Introductionmentioning
confidence: 99%